Beispiel Nr: 09
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ -\frac{1}{2}x +1y =2\\ \frac{1}{2}x -3y = -3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad -\frac{1}{2} x +1 y =2\\ II \qquad \frac{1}{2} x -3 y = -3 \\ \text{I nach x auflösen}\\ -\frac{1}{2} x +1 y =2 \\ -\frac{1}{2} x +1 y =2 \qquad /-1 y\\ -\frac{1}{2} x =2 -1 y \qquad /:\left(-\frac{1}{2}\right) \\ x =-4 +2 y \\ \text{I in II}\\ \frac{1}{2} (-4 +2 y ) + -3 y = -3 \\ -2 +1 y -3 y = -3 \qquad / -\left(-2\right) \\ +1 y -3 y = -3 -\left(-2\right) \\ -2 y = -1 \qquad /:\left(-2\right) \\ y = \frac{-1}{-2} \\ y=\frac{1}{2} \\ x =-4 +2 y \\ x =-4 +2 \cdot \frac{1}{2} \\ x=-3 \\ L=\{-3/\frac{1}{2}\} \end{array} & \begin{array}{l} I \qquad -\frac{1}{2} x +1 y =2\\ II \qquad \frac{1}{2} x -3 y = -3 \\ \text{I nach y auflösen}\\ -\frac{1}{2} x +1 y =2 \\ -\frac{1}{2} x +1 y =2 \qquad /+\frac{1}{2} x\\ 1 y =2 +\frac{1}{2}x \qquad /:1 \\ y =2 +\frac{1}{2}x \\ \text{I in II}\\ \frac{1}{2}x + -3(2 +\frac{1}{2} x ) = -3 \\ -6 -1\frac{1}{2} x -3 x = -3 \qquad / -\left(-6\right) \\ -1\frac{1}{2} x -3 x = -3 -\left(-6\right) \\ -1 x = 3 \qquad /:\left(-1\right) \\ x = \frac{3}{-1} \\ x=-3 \\ y =2 +\frac{1}{2} x \\ y =2 +\frac{1}{2} \cdot \left(-3\right) \\ y=\frac{1}{2} \\ L=\{-3/\frac{1}{2}\} \end{array} \end{array} $